Implementasi Metode Poster Comment dalam Pembelajaran Al-Qur’an Hadis di Madrasah Aliyah Muhammad Basiuni Imran Sambas - Nilda Nilda (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to determine the implementation of the poster comment method in learning the Qur'an and Hadith in eleventh grade at Madrasah Aliyah Muhammad Basiuni Imran Sambas. Poster comment is one of many learning methods. The implementation of the poster comment method in learning the Qur'an and Hadith is a learning activity that uses the poster comment method, where students are required to express their ideas and thoughts according to the teacher's instructions. For the poster comment method to run smoothly and effectively, planning is required before the implementation process. Finally, the results of the poster comment method implementation in learning the Qur'an and Hadith can be determined whether this poster comment method is suitable for implementation in the classes selected for the study. This study used a qualitative approach. The results showed that the use of the poster comment method resulted in high enthusiasm and active participation in the lesson. Several students presented to the front of the class carrying cardboard with pictures on it. The students who presented were very active in delivering their presentations in learning the Qur'an and Hadith.